SECONDARY SCHOOL PARTICIPATION PRACTICES. FROM THE NORMATIVE FRAMEWORK TO THE EXPERIENCES AND IMPORTANCE THAT MOTHERS AND SCHOOL MEMBERS ATTRIBUTE TO THE ´SCHOOL, FAMILIES AND COMMUNITY NATIONAL SESSIONS - Mariana Cecilia Ojeda; María Gloria Saucedo (Revista del Instituto de Investigaciones en Educación, 2015)
This study aims at sharing the partial results from a research scholarship project, with regard to the participation difficulties of families and teachers in school practices taking place at secondary school. This work is in agreement with a line of research about educational policies and teachers´ work at secondary schools, from the Education Research Institute at the UNNE Humanities Faculty. Our objective is to describe and analyze the School, Families and Community National Sessions from a discursive level to its implementation in educational institutions; the experiences and their significance for mothers and school members. The study is developed from pedagogical theory and from educational sociology insights. The methodology employed is in accordance with a qualitative design of exploratory nature. To this matter, different techniques for data collection were considered relevant. In-depth interviews to different members, participant observation in three working sessions and the researcher field journal. The compiled information was methodologically analysed through a variety of strategies and techniques. As a result we identified that there are some underling complains, rejections, agreements and disagreements as regard the session calls, and the importance people attribute to their participation in the sessions. The process that was intended to be participatory, from the normative framework, is here relativized by people, in connection to what they imagine “the other and the others can do”.